2018
DOI: 10.1093/neuonc/noy095
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labeling MR imaging for differentiation between high- and low-grade glioma—a meta-analysis

Abstract: Arterial spin labeling MR imaging had an excellent diagnostic accuracy for differentiation between high-grade and low-grade glioma. Given its low cost, non-invasiveness, and efficacy, ASL MR imaging should be considered for implementation in the routine workup of patients with glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 46 publications
3
34
0
1
Order By: Relevance
“…They also concluded that rCBF was significantly higher in medulloblastoma compared with pilocytic astrocytoma ( p < 0.05) ( 21 ). Our findings were very consistent with these previous studies ( 18 21 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…They also concluded that rCBF was significantly higher in medulloblastoma compared with pilocytic astrocytoma ( p < 0.05) ( 21 ). Our findings were very consistent with these previous studies ( 18 21 ).…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, the accurate diagnosis and grading of gliomas are crucial because these factors influence the decision-making process for treatment and prognosis (11)(12)(13). ASL has been used to evaluate the penumbra area, such as during cerebral infarction, and has also been effective for assessing brain tumors and neurodegenerative disorders, such as Alzheimer's disease, dementia, and Parkinson's disease (16,17). Recently, some studies have shown that ASL-measured CBF can differentiate between low-and high-grade astrocytomas (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a widely available and non-invasive medical imaging tool and the only modality to deliver information of brain tissue at a sufficient contrast, spatial and temporal resolution [5,6]. While conventional MRI techniques assess anatomical information about the structure of brain tissue and vasculature, advanced MRI techniques can measure dynamic and functional processes such as perfusion [using arterial spin labeling (ASL), dynamic contrast enhanced (DCE), and dynamic susceptibility contrast (DSC)] [7,8], metabolism [using MR spectroscopy (MRS)] [9], microstructure [using diffusion kurtosis imaging (DKI), intravoxel incoherent motion (IVIM) [10], and other diffusion MRI techniques] [11][12][13], stiffness [using magnetic resonance elastography (MRE)] [14], oxygen extraction [using BOLD-MRI] [15], and vessel architecture [using vessel architectural imaging (VAI)] [16]. Examples of these conventional and advanced MRI techniques are provided in Fig.…”
Section: State-of-the-art Mr Imaging For Gliomamentioning
confidence: 99%
“…29 A recent meta-analysis has demonstrated that ASL is clinically useful in differentiating glioma grades on both PASL and pCASL. Falk Delgado et al 7 analyzed 15 studies with 505 patients and demonstrated that ASL helps to differentiate between high-grade and low-grade gliomas with a summary sensitivity of 0.89 (95% CI 0.79-0.90) and specificity of 0.80 (95% CI 0.72-0.89). High-grade gliomas have a significant increase in all ASL perfusion values such that absolute tumor blood flow and maximum mean relative tumor blood flow aid in grading gliomas.…”
Section: Gliomasmentioning
confidence: 99%